Bioactive Compounds and Adipocyte Browning Phenomenon - Josué Manríquez-Núñez; Minerva Ramos-Gómez (Current Issues in Molecular Biology, 2022)
Overweight and obesity have become worldwide health issues in most countries. Current strategies aimed to prevent or reduce overweight and obesity have mainly focused on the genes and molecular mechanisms that give the functional characteristics to different types of adipose tissue. The Browning phenomenon in adipocytes consists of phenotypic and metabolic changes within white adipose tissue (WAT) activated by thermogenic mechanisms similar to that occurring in brown adipose tissue (BAT); this phenomenon has assumed great relevance due to its therapeutic potential against overweight and obesity. In addition, the study of inflammation in the development of overweight and obesity has also been included as a relevant factor, such as the pro-inflammatory mechanisms promoted by M1-type macrophages in adipose tissue. Studies carried out in this area are mainly performed by using the 3T3-L1 pre-adipocyte cell line, testing different bioactive compound sources such as plants and foods; nevertheless, it is necessary to standardize protocols used in vitro as well to properly scale them to animal models and clinical tests in order to have a better understanding of the mechanisms involved in overweight and obesity.